What drives fraud in a credence goods market? Evidence from a field study - Alexander Rasch; Christian Waibel (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2015)
This paper investigates the impact of four key economic variables on an expert firm's incentive to defraud its customers in a credence goods market: the level of competition, the expert firm's financial situation, its competence, and its reputational concerns. We use and complement the dataset of a nationwide field study conducted by the German Automobile Association that regularly checks the reliability of garages in Germany. We find that more intense competition and high competence lower a firm's incentive to overcharge. A low concern for reputation and a critical financial situation increase the incentive to overcharge.
Keywords: D82; L15; 330; Asymmetric information; Auto repair market; Credence goods; Expert; Fraud; Overcharging